Exploring Women’s Agency and Empowerment in Developing Countries : Where Do We Stand? - Hanmer, Lucia; Klugman, Jeni (Taylor and Francis, 2015)
While central notions around agency are well established in academic literature, progress on the empirical front has faced major challenges around developing tractable measures and data availability. This has limited our understanding about patterns of agency and empowerment of women across countries. Measuring key dimensions of women's agency and empowerment is complex, but feasible and important. This paper systematically explores what can be learned from Demographic and Health Survey (DHS) data for fifty-eight countries, representing almost 80 percent of the female population of developing countries. It is the first such empirical investigation. The findings quantify some important correlations. Completing secondary education and beyond has consistently large positive associations, underlining the importance of going beyond primary schooling. There appear to be positive links with poverty reduction and economic growth, but clearly this alone is not enough. Context specificity and multidimensionality mean that the interpretation of results is not always straightforward.